Model Aksi Insiden Berbasis Classroom sebagai Alternatif dalam Meningkatkan Kemampuan Menulis Teks Eksplanasi Siswa pada Masa Pandemi Covid-19 - Nora Vitaria (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
This study aims to describe the application of the classroom-based incident action model in improving students' explanatory text writing skills during the Covid-19 pandemic. The research method used was Classroom Action Research with the model of Kemmis and Mc Taggart. This classroom action research was conducted in 2 cycles. Each cycle has 2 meetings. The research subjects were students of class XI IPA 1 SMAN 8 Bengkulu City, school year 2020/2021. The instruments used were tests and non-tests. Data collection techniques through 1). Documentation in the form of Geogle Classroom, Geogle From, and Geogle Docs applications, 2) tests in the form of multiple choice tests and essays, and 3) questionnaires, to determine student responses to the application of classroom-based incident action models. The analysis step is through data reduction, data presentation, and conclusion drawing. The results showed that the application of the classroom-based incident action model was able to improve the ability to write explanatory text during the Covid-19 pandemic. This is indicated by before applying the incident action model students obtained learning outcomes with an average score of 73.44 in the Good category and increased after the implementation of the incident action model with an average score of 83.16 in the Very Good category. The result of cycle 1 to 2 increased by 1.16%. Then, the results of the questionnaire obtained were 63.75% of students agreed that the classroom-based incident action model was applied during the Covid-19 pandemic, obtained in the Good category. The classroom-based incident action model has the advantage of being able to increase student creativity when writing explanatory text activities because each individual in the group contributes ideas in the form of explanatory writing.